PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI PENDEKATAN SAINTIFIK PADA MATERI MEDAN MAGNET KELAS XII SMA - Sania Syamsul; Muhammad Syafi’i; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The education system oriented to the 2013 Curriculum places more emphasis on student activity (student center) which is oriented towards attitudes and skills. In addition, student activity is still low, the delivery of material in one direction results in the lack of training in students' science process skills, and there are some learning materials that are abstract in nature, which are difficult to understand, resulting in difficulties in understanding physics learning. So that research is carried out on the development of scientific approach-oriented learning tools on the material of the XII SMA class Magnetic Field. The type of research used is Research and Development (R&D) using a 4D model which is carried out only up to the development stage. The types of data to be obtained in this study are quantitative and qualitative data. Quantitative data is in the form of validity values from learning tools, and qualitative data is obtained from criticism and suggestions from validators. The data collection instrument used is in the form of a learning device validation sheet. The data were analyzed descriptively to determine the validity of the learning device. The results showed that the validity of the learning device as a whole obtained a valid category, so that it was declared worthy of use in learning. Key Words: Physics Learning Device, Scientific Approach, Magnetic Field